Political change and territoriality in indonesia : privincial proliferation - Kimura, Ehito (Milton Park, Abingdon, Oxon ; New York : Routledge, 2013)
"What makes large, multi-ethnic states hang together? At a time when ethnic and religious conflict has gained global prominence, the territorial organization of states is a critical area of study. Exploring how multi-ethnic and geographically dispersed states grapple with questions of territorial administration and change, this book argues that territorial change is a result of ongoing negotiations between states and societies where mutual and overlapping interests can often emerge. It focuses on the changing dynamics of central-local relations in Indonesia. Since the fall of Suharto's New Order government, new provinces have been sprouting up throughout the Indonesian archipelago. After decades of stability, this sudden change in Indonesia's territorial structure is puzzling. The author analyses this "provincial proliferation", which is driven by multilevel alliances across different territorial administrative levels, or territorial coalitions. He demonstrates that national level institutional changes including decentralization and democratization explain the timing of the phenomenon. Variations also occur based on historical, cultural, and political contexts at the regional level. The concept of territorial coalitions challenges the dichotomy between centre and periphery that is common in other studies of central-local relations."--Publisher's description.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Central-local government relations -- Indonesia; Indonesian provinces; Decentralization in government -- Indonesia; Indonesia -- Administrative and political divisions; Indonesia -- Politics and government -- 1998-; Electronic books